DETERMINANT EXECUTORS OF THE EFFECTIVENESS OF TOURISM DEVELOPMENT POTENTIALS AND ITS DEVELOPMENT MODEL IN SAROLANGUN REGENCY, JAMBI, INDONESIA - Novita Wulandari (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
This study aims to analyze the Effect of Policy Implementation, Investment, and Business Executors on the Effectiveness of Tourism Potential Development in Sarolangun Regency, Jambi Province. This research uses a quantitative approach with explanatory research type, with a population of 74,660 people and a sample of 100 people determined by the Slovin formula. Data collection techniques in this study were using documentation, observation, questionnaire, and literature techniques. The results of the study prove that Policy Implementation has an effect of 51.3%, Investment has an effect of 15.5%, Business executors have an effect of 52.6%, Policy Implementation, Investment and Entrepreneurs together have a 52.8% effect on the Effectiveness of Tourism Development. Recommendations from the results of this study are that the implementation of the policy must be supported by a law on tourism and RIPPARDA. Thus, mapping the tourism area which is supported by multi-stakeholder policies and cooperation, will open up large investment opportunities in the tourism sector. Organizational restructuring of the regional tourism office as a business executor from a structural dimension. These three variables must get attention, so they can form quality human resources for the benefit of tourism development in Sarolangun Regency. Keywords: Policy Implementation, Investment, Business Executors, Effectiveness and Tourism